The effect of young pepaya leaf ethanol extract (Carica papaya L.) with concentration variants on the growth of pathogenic Streptococcus pyogenes bacteria causing pharyngitis through in vitro testing - I Gede Krisna Putra Yasa; Agung Nova Mahendra; Bagus Komang Satriyasa (Intisari Sains Medis, 2019)
Background: Pharyngitis infection issues by Streptococcus pyogenes bacteria have been increasing worldwide, and antibiotic resistance to the bacterium treatment also continues to escalate. Young papaya leaves (Carica papaya L.) have a bactericidal and bacterostatic effect (include papain, flavonoids, alkaloids (karpain alkaloids), saponins, glycosides, phenols (tacophenol), and tannins) that can be an option for treatment of pharyngitis infections other than drugs. This study aims to determine the effectiveness of ethanol extract of young papaya leaves (Carica papaya L.) in inhibiting the growth of Streptococcus pyogenes bacteria through in vitro testing.Methods: This study was a true-post experimental study using control group design. The sample was divided into 2 groups: positive and negative control groups as well as treatment groups with concentration variants of 25%, 50%, 75%, and 100%. Data were analyzed using SPSS version 17 software for windows.Results: The result obtained from this study showed that papaya leaf extract (Carica papaya L.) was proven to significantly inhibit the growth of Streptococcus pyogenes bacteria at concentrations of 25% to 100% with an average diameter of the inhibition zone of 6.4 mm to 7.4 mm (P<0.05).Conclusion: This evidences that the ethanol extract of young papaya leaves (Carica papaya L.) with various concentrations does exhibit an influence on the growth of Streptococcus pyogenes bacteria.